Evaluación y propuesta de mejora mediante gestión del conocimiento aplicada al programa PIN UNO, PIN DOS, PIN DANE del Departamento Administrativo Nacional de Estadística (DANE) (2017)
Knowledge Management provides methods, tools and strategies in order to take advantage of the knowledge in our organizations and generate new knowledge. This article summarizes proposals to improve the program PIN UNO, PIN DOS, PIN DANE and subsequent programs in the organization. These proposals were generated as a result of applying the knowledge management vision (evaluation, identification, encoding, creation, transfer, protection and application) and the use of the CommonKADS methodology.